Participatory approaches for sustainable land use in Southeast Asia - Neef, Andreas 1965- (White Lotus Press, 2005)
Participatory approaches for sustainable land use in Southeast Asia (ed. Andreas Neef) comprises in-depth analyses and discussion of Participatory Research and Development in action with emphasis on the needs of rural communities in marginal regions of Cambodia, Indonesia, Lao P.D.R., Nepal, the Philippines, South China, Thailand and Vietnam. Examples from the field cover the participatory development of soil and water conservation technologies, gender-sensitive participatory methodologies, participation in priority-setting for agricultural research, the use of Geographic Information Systems in supporting participatory processes, and the benefits of using local knowledge in managing natural resources. While the contributions contain a wealth of methodological innovations and conceptual advances in participatory approaches, they also point to the conceptual and political limitations and various dangers of misuse of participation in research and development programmes. Several chapters provide evidence that a supportive institutional and socio-political framework is conditional for successfully scaling-up and institutionalising participatory processes in government agencies and research organisations. Only then participatory approaches will remain relevant beyond the fashionable rhetoric of the mainstream participatory discourse